Trimethoprim-sulfamethoxazole induced toxic epidermal necrolysis: a case report - Bhosale, Rama R.; Bodke, Pradeep S.; Patil, Abhishek V.; Bhurke, Shivaji H. (International Journal of Basic & Clinical Pharmacology, 2017)
Toxic epidermal necrolysis (TEN) is a rare but serious dermatological disorder commonly caused as an idiosyncratic reaction to drugs and the most common drugs implicated are antibiotics, anticonvulsants and non-steroidal anti-inflammatory drugs. Here, we report a case of trimethoprim-sulfamethoxazole induced TEN in a 26 years old female.